ARESTOP BULLYING SONGS USED EFFECTIVELY TO STOP BULLYING BEHAVIOR IN ADOLESCENTS? - AGOES DARIYO (ARTISTIC : International Journal of Creation and Innovation, 2023)
Bullying victims feel psychologically traumatized by the malevolentbullying behavior perpetrated by an individual or group of people. They suffer from psychological distress, including depression, social anxiety, social withdrawal, fear of recurrence, and in severe cases, suicidal ideation.Meanwhile,bullying perpetrators fail to comprehend the adverse consequences resulting from their actions. It is imperative that prior bullying cases are not repeated and are promptly handled, prevented, and halted. One effective method to combat bullying behavior is to produce artistic creations in the form of anti-bullying songs. This study is a research project that utilizes the ADDIE approach (Analysis, Design, Development, Implementation, and Evaluation). The data collection method employed a questionnaire encompassing several elements of poetry, rhythm, beat, style, tempo, instrument, and visual display. The sample technique employed was purposive sampling, resulting in 87 participants. Utilizing the ADDIE idea, this study employed a thematic method for data analysis. The findings indicate that the development of anti-bullying songs has adhered to the ADDIE framework. Stop bullying songs have fulfilled the criteria of excellent musical compositions, including lyrics that are easily comprehensible (77 = 88.6%), melody (71 = 81.6%), rhythm (74 = 85.1%), beat (73 = 83.9%), style (73 = 83.9%), tempo (76 = 87.4%), and instruments (70 = 80.5%). Moreover, the stop-bullying songswere efficient in curbing bullying tendencies among adolescents(73 = 83.9 %).